2022
DOI: 10.1029/2022gl097794
|View full text |Cite
|
Sign up to set email alerts
|

Regional Signatures of Forced North Atlantic SST Variability: A Limited Role for Aerosols and Greenhouse Gases

Abstract: During the 20th century, North Atlantic sea surface temperatures (SSTs) displayed a basin-wide, multidecadal oscillation superimposed on to a century-scale warming tendency associated with a global response to external radiative forcing. The slow, oscillating part of basin-wide SST variations, separate from the century-scale warming, has been considered unique to the North Atlantic and became known as the Atlantic Multidecadal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…However, aerosol effects are much more heterogeneous both in time and space, due to strong regional patterns of emission changes and indirect effects through interactions with clouds. Many studies have shown potential anthropogenic aerosol impacts on decadal climate including AMV (Booth et al, 2012;Bellucci et al, 2017;Murphy et al, 2017;Bellomo et al, 2018;Watanabe and Tatebe, 2019), Atlantic Meridional Overturning Circulation (AMOC, Menary et al, 2020;Hassan et al, 2021), the Aleutian Low and Pacific Decadal Variability (PDV, Allen et al, 2014;Takahashi and Watanabe, 2016;Oudar et al, 2018;Wilcox et al, 2019;Dittus et al, 2021;Dow et al, 2021), mid-latitude atmospheric jets (Wang Y. et al, 2020;Dong et al, 2022), southern hemisphere atmospheric circulation (Gillett et al, 2013;Rotstayn et al, 2013;Wang H. et al, 2020), Atlantic hurricanes (Mann and Emanuel, 2006;Dunstone et al, 2013), Sahel rainfall (Ackerley et al, 2011;Marvel et al, 2020;Hirasawa et al, 2022), and monsoon rainfall (Bollasina et al, 2011;Polson et al, 2014;Ma et al, 2017;Zhou et al, 2020), though aerosol indirect effects are particularly uncertain and these links are still debated (Oudar et al, 2018;Zhang R. et al, 2019;Baek et al, 2022).…”
Section: Potential Drivers Of Multi-annual To Decadal Changes In Climatementioning
confidence: 99%
“…However, aerosol effects are much more heterogeneous both in time and space, due to strong regional patterns of emission changes and indirect effects through interactions with clouds. Many studies have shown potential anthropogenic aerosol impacts on decadal climate including AMV (Booth et al, 2012;Bellucci et al, 2017;Murphy et al, 2017;Bellomo et al, 2018;Watanabe and Tatebe, 2019), Atlantic Meridional Overturning Circulation (AMOC, Menary et al, 2020;Hassan et al, 2021), the Aleutian Low and Pacific Decadal Variability (PDV, Allen et al, 2014;Takahashi and Watanabe, 2016;Oudar et al, 2018;Wilcox et al, 2019;Dittus et al, 2021;Dow et al, 2021), mid-latitude atmospheric jets (Wang Y. et al, 2020;Dong et al, 2022), southern hemisphere atmospheric circulation (Gillett et al, 2013;Rotstayn et al, 2013;Wang H. et al, 2020), Atlantic hurricanes (Mann and Emanuel, 2006;Dunstone et al, 2013), Sahel rainfall (Ackerley et al, 2011;Marvel et al, 2020;Hirasawa et al, 2022), and monsoon rainfall (Bollasina et al, 2011;Polson et al, 2014;Ma et al, 2017;Zhou et al, 2020), though aerosol indirect effects are particularly uncertain and these links are still debated (Oudar et al, 2018;Zhang R. et al, 2019;Baek et al, 2022).…”
Section: Potential Drivers Of Multi-annual To Decadal Changes In Climatementioning
confidence: 99%
“…(2022). The modeling framework of “Single Model Initial‐condition Large Ensembles” (LEs; Deser et al., 2020), which provides a priori knowledge of forced and internal contributions in any individual simulation, has served as an effective testbed for evaluating these and other methods (Baek et al., 2022; DP21; Frankignoul et al., 2017; Q20).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, simple procedures such as subtracting global‐mean temperature (Trenberth & Shea, 2006) or linear detrending (Enfield et al., 2001; Murphy et al., 2017) alias the pattern of forced climate change onto the structure of internal AMV (iAMV) as shown by Deser and Phillips (2021; hereafter DP21) and Baek et al. (2022). The modeling framework of “Single Model Initial‐condition Large Ensembles” (LEs; Deser et al., 2020), which provides a priori knowledge of forced and internal contributions in any individual simulation, has served as an effective testbed for evaluating these and other methods (Baek et al., 2022; DP21; Frankignoul et al., 2017; Q20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is emerging evidence that AAs have played an important role in shaping the recent Atlantic variability, there remain a number of inconsistencies with the real world, and so questions remain. For example, many studies have shown that the externally forced AMV SST pattern has significant differences to the observed, particularly in the SPNA [ 80 , 81 ]. Furthermore, the mechanisms that are usually invoked to explain the impact of AA forcing on the North Atlantic SST assume AA impacts AMV only through changes in the surface heat budget (i.e.…”
Section: Introductionmentioning
confidence: 99%